2014
DOI: 10.1016/j.btre.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Relative examination of antioxidative enzymatic activities in plantlets of Cardiospermum halicacabum L. differentiated from hypocotyls in in vivo and ex vitro environment

Abstract: A plant regeneration protocol was devised for Cardiospermum halicacabum by means of aseptically extracted 7 days old hypocotyls forming adventitious shoots on Murashige and Skoog (MS) medium harmonized with 0.7 μM thidiazuron (TDZ) producing a maximum of 18.20 ± 0.98 number of shoots in 94% cultures following 4 weeks. Subsequent subculturing for five passages, on a medium without plant growth regulators, tempted the highest shoot number (40.00 ± 1.15) with an average shoot length of 6.53 ± 0.49 cm after the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…They also found a positive correlation between days of sub culturing and antioxidant enzyme production, but the increase was not linear. Anushi et al [21] have also found increased SOD activity when plantlets of Cardiospermum helicacabum L. were treated with plant growth regulators, and their results also support our findings. Similarly, Zaheer et al [40] have shown increased SOD levels in wheat seeds when they were soaked in different combinations of plant growth regulators.…”
Section: Antioxidant Enzyme Activities In Response To the Applicationsupporting
confidence: 91%
See 2 more Smart Citations
“…They also found a positive correlation between days of sub culturing and antioxidant enzyme production, but the increase was not linear. Anushi et al [21] have also found increased SOD activity when plantlets of Cardiospermum helicacabum L. were treated with plant growth regulators, and their results also support our findings. Similarly, Zaheer et al [40] have shown increased SOD levels in wheat seeds when they were soaked in different combinations of plant growth regulators.…”
Section: Antioxidant Enzyme Activities In Response To the Applicationsupporting
confidence: 91%
“…Catalase activity was comparatively high in 21-day-old rather than 14-day-old tissue-cultured raised plantlets. Anushi et al [21] also found an increase in CAT level after 4 weeks as compared to 2-week-old in vitro-regenerated shoots.…”
Section: Antioxidant Enzyme Activities In Response To the Applicationmentioning
confidence: 89%
See 1 more Smart Citation
“…Anushi et al [32] found an increase in CAT and SOD activity in plantlets of Cardiospermum halicacabum L. in in vivo and ex vitro environment with the passage of time. They also found increases in CAT and SOD activity during the acclimatization period when plantlets were transferred into the soil.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…Recently, there has been a growing interest to study the reactive oxygen species (ROS) and the antioxidant defense mechanisms during shoot organogenesis, embryogenesis and ex vitro acclimatization of in vitro-derived plants (Gupta and Datta 2003;Jahan et al 2014). Under in vitro conditions, plants experience significant stress while exposed to extreme culture conditions (low light intensity, high relative humidity, limited gaseous exchange, higher sucrose or nitrogen levels and exogenous growth hormones) resulting in morphological and physiological disorders (Ahmed and Anis 2014a, b).…”
Section: Introductionmentioning
confidence: 99%